PERAN TATA GUNA LAHAN TERHADAP DISTRIBUSI TINGKAT KERAWANAN EROSI DI KAWASAN CILETUH JAWA BARAT - Sulaksana, Nana; Sjafrudin, Achmad; Sukiyah, Emi; Raditya, Pradnya P.; Abdulah, Fikri; Setiyanto, Puguh (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
Ciletuh located in Ciemas district, Sukabumi, West Java is known by its geological diversity (geodiversity). This area is located at the southwestern of Java Island and directly adjacent to the Indian Ocean. Ciletuh is a very attractive tourist visits area and deserve to be visited. This area is planned to be a National Geopark area and Global Geopark Network in 2016. This will certainly have an impact on the change of land use in the next few years. The change of land use will affect indirectly to the distribution of erosion rate in research area. The higher of land use changes, the higher of erosion rate that can cause environmental quality degradation. This research aims to reveal the land use changes can affect the level of of vulnerability to erosion in Ciletuh. This research method uses laboratory and studio analysis. Remote sensing analysis is used to delineate land use. The distribution rate of erosion in research area can be known through erosion calculation formula. Based on delineation of land use, Ciletuh have areas of land cover consisting of 6.666.104 m2 (9,7%) plantation, 10.444.567 m2 (15,2%) forests, 3.252.843 m2 (4,7%) settlements, 82.264 m2 (0,1%) swamps, 22.863.874 m2 (33,3%) paddy fields, 19.474.346 m2 (28,37%) bushes, 2.057.689 m2 (2,9%) vacant lands, and 3.788.699 m2 (5,5%) moors area. The result of early research identification indicates that the level of vulnerability to erosion associated with the greatest land cover is moor and vacant lands.